Do young adult males aiming to improve strength or develop muscle hypertrophy train according to the current strength and conditioning recommendations? - Pablo Prieto González; Jorge Sánchez-Infante; Luis Miguel (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The present study aimed to verify if young adult males who aimed to improve their strength or attain muscle hypertrophy trained in agreement with the current strength and conditioning guidelines. Methods: Four hundred and fourteen subjects aged 18-25 with less than one year of strength training experience and whose training goal was to increase their strength or develop muscle hypertrophy were finally included in this research. They were surveyed through an 18-item self-administered questionnaire to verify whether their strength training practices met the current strength training guidelines. Results: Overall, more than 50% of the respondents did not follow the current strength and conditioning recommendations related to muscle action, number of sets, training structure, type of resistance, training to failure, and training supervision. Only slightly more than 50% of them did not train in agreement with the recommendations regarding exercise selection, number of repetitions, and weekly training frequency. The level of compliance with the training objectives of the respondents who followed the current strength and conditioning guidelines related to exercise selection, rest, speed, type of resistance, and training supervision was higher than specific cohorts who did not. Conclusion: Training in agreement with the current strength and conditioning guidelines would ensure that young adult males with less than one year of strength training experience attain their training objectives to a greater extend. Subjects who practice strength training should follow those strength and conditioning guidelines to avoid limiting future adaptations and increase the variability of their training programs, thus preventing workout plateau and fostering motivation.